Molecular engineering toward coexistence of dielectric and optical switch behavior in hybrid perovskite phase transition material - Hu, Yuzhong (2019)
Organic–inorganic hybrid perovskites with considerable dielectric differences near the phase transition are potential candidates as phase transition materials (PTMs). However, compared with traditional PTMs, which require multiple switchable channels, the hybrid perovskites so far show only switching behavior in dielectric constants. We herein report a new crystal design strategy and successful synthesis of a two-dimensional perovskite (C6H5C2H4NH3)2MnCl4. In this hybrid perovskite, the manganese chloride octahedron is a crystal field sensitive luminescent molecular system. The distortion level of MnCl64– also depends on temperature during the order–disorder phase transition. Hence, such a manganese octahedron-based perovskite can exhibit switching behaviors in both dielectric and optical properties. We observe a 14% decrease in optical absorption and 1.6 times increase in dielectric constant during the phase transition at 365 K. In addition, the characteristic photoluminescence decreases by 17% in intensity. Such a molecule-based crystal design paves a new way to explore multifunctional PTMs based on organic–inorganic perovskites.